Evaluation of Runoff and Sediment in the Marl Outcropping in East Azerbaijan - Ahad Habibzadeh; Mohammadreza Nikjoo; Hamidreza Peyrovan (نشریه جغرافیا و برنامه‌ریزی, 2013)
Marl units in territory-watershed basin in East Azerbaijan province have expanded significantly, and cause natural malformation, including soil erosion, erosion facieses types (surface, rill-gully) and sedimentation in the basin. In this study, digitized geological stratigraphy and lithology maps that were prepared. Marlstone regions were drawn, Accordingly, three units, including Eocene, Miocene and Cretaceous marlstone were determined. The climate and slope maps of the province were crossed in GIS system and ILwis software and final maps of the area and working units were determined. Amount of runoff and sediment on marlstone regions were measured using artificial showers. Results indicated that the correlation coefficient of topographic slope was equal to the amount of runoff 0.479 and the statistical significance of their relationship together. Simple correlation coefficient between runoff and sediment calculated to be (0.452) and their relationship was acceptable was significantly meaningful. Correlation coefficient between the amount of sediment from soil erosion caused by rain instrument with organic carbon neutral materials were equal to -0.374 and are -0.382.